Predicting consumer attitude to use on-line shopping: context of Malaysia - Jadehkenari, Marzieh Zendehdel; Paim, Laily (Marsland Press, 2013)
Nowadays, the Internet has become an essential part of our lives. It has entered all sectors of our daily activities: business, communication, Shopping, and personal life. This study, based on the diffusion of innovations (DOI) theory investigates factors that influence adoption and usage of e-shopping, especially, in Malaysia. Factors were empirically tested against data collected from 375 participants using survey questionnaires. Perceived Relative advantage was found to be the most significantly related factor affecting e-shopping adoption in Malaysia, followed in turn by Privacy and Compatibility. Security of the Internet had a notable effect on e-shopping and adoption in Malaysia. However there is no significant in consumers’ attitude towards online shopping based on complexity. The results show that if students worry about whether their information due to the process of online shopping will be used for other purposes, it will reduce their purchase attitude. In other words, students will evaluate online shopping based on such perceptions as whether the purchase through online will bring additional advantages, and, at the same time, be compatible with their current life style. Customers shop online to save time and effort.